Modelling the utilization rates of pedestrian crosswalks - Walid Abdullah, Al Bargi (2023)
A zebra crossing is a form of pedestrian crossing provision point on roads that have significant volumes of traffic. It is one of the safety measures employed to reduce avoidable pedestrian-motorist conflicts and accidents on such roads. In the past several studies have been conducted on the behaviours of road users (pedestrians and motorists) especially on non-signal intersections. Although, various recommendations and solutions have been proffered to the many road-crossing challenges. But there has been little to no change in pedestrians’ perceptions and preferences of zebra crossing. Contemporary researches have tried to rectify this by applying several models to rate the use of pedestrian zebra crossing. This study uses a Regression Model Techniques to analyse factors influencing utilization rate of pedestrian zebra crossing. In this study, 450 samples were collected from 12 locations, covering school, public building, residential and business areas to examine the utilization rate of the zebra crossing by pedestrians. To examine the significance level on the crossing utilization rates by pedestrian at 95% confidence interval, a pedestrian utilization rate (PUR) was acting as the dependent variable and the remaining variables served as the independent variables. The Multiple Linear Regression (MLR) model was also used to determine the utilization rate needed to develop the zebra crossing utilization model. From the findings, the calibrated R2 value was discovered to be at 0.937 and the descriptive statistics of MLR test, t and p-values, were also found within an acceptable range. The result also showed that, out of all the variables which were used, only three have a significant effect on the utilization rates of pedestrian zebra crossing while the remaining variables have an insignificant effect. The study concluded that among the different variables, Guardrail, number of lanes and Width of zebra crossing were the most influential variables. It is believed that the conclusions drawn from this research are expected to be useful to improve the state of pedestrian facilities in Malaysia.